1966
DOI: 10.1126/science.154.3750.771
|View full text |Cite
|
Sign up to set email alerts
|

Nebraskan and Kansan Stades: Complexity and Importance

Abstract: Several Early Pleistocene stadial tills and related soils in Kansas and Nebraska indicate a complex history of ice-sheet fluctuations. It is impossible to assign ages to individual till sheets solely on the basis of position in a stratigraphic column; all Early Pleistocene correlations must be reevaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…There is no evidence that later Illinoian and Wisconsinan advances ever reached as far south as Kansas and Missouri. Bayne (1968) and Dort (1965Dort ( , 1966Dort ( , 1985 described several tills in northeastern Kansas (Fig. I), suggesting a more complex record similar to that of pre-Illinoian glacial deposits in Iowa and Nebraska (Boellstorff 1973;Hallberg 1980Hallberg , 1986.…”
Section: Previous Workmentioning
confidence: 96%
“…There is no evidence that later Illinoian and Wisconsinan advances ever reached as far south as Kansas and Missouri. Bayne (1968) and Dort (1965Dort ( , 1966Dort ( , 1985 described several tills in northeastern Kansas (Fig. I), suggesting a more complex record similar to that of pre-Illinoian glacial deposits in Iowa and Nebraska (Boellstorff 1973;Hallberg 1980Hallberg , 1986.…”
Section: Previous Workmentioning
confidence: 96%
“…Early studies identified two tills north of Kansas City, which were assigned a Nebraskan and Kansan age based on stratigraphic position and relation to palaeosols. Bayne (1968) and Dort (1965Dort ( , 1966Dort ( , 1985 described several tills in northeastern Kansas (Fig. There is no evidence that later Illinoian and Wisconsinan advances ever reached as far south as Kansas and Missouri.…”
Section: Previous Workmentioning
confidence: 99%
“…The simple two-till, one-ash stratigraphy for Kansas and adjacent states began to unravel during the 1960s and 1970s with discovery of multiple till units representing more than two glacial advances (Reed & Dreeszen 1965;Reed et al 1965;Dort 1966;Bayne 1968;Boellstorff 1978a;Easterbrook & Boellstorff 1981). New stratigraphic names and type sections were designated in Nebraska and Kansas by Reed & Dreeszen (1965), and new long-distance correlations were proposed between Kansas and regions to the north (Bayne et al 1971).…”
Section: Revision Of Glacial Stratigraphymentioning
confidence: 99%
“…(1971), and Aber (1985a) recognized three till units. Dort (1966Dort ( , 1985 interpreted five episodes of glacier advance at one site in Doniphan County; interpretation of this site is problematic, however, because of repetition in the section due to ice thrusting. Confusion is evident in terminology and varying interpretations.…”
Section: Lithostratigraphy Of Glacial Deposits In Kansasmentioning
confidence: 99%